Transformasi Sikap Hidup Masyarakat Majemuk dalam Pembelajaran Pendidikan Agama Kristen - Nova Maelissa (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
Indonesia, as a multicultural nation, has diversity that includes religious, ethnic, cultural, racial, and gender diversity, as well as socio-political dynamics. This plurality is a social asset, but it also has the potential to cause conflict if it is not managed through an inclusive and tolerant attitude. This article aims to analyze the transformation of the attitudes of a diverse society through Christian Religious Education in the context of Indonesian education. This study uses a qualitative approach with a literature review method through a critical analysis of literature on multicultural education, recognition politics, inclusive religious education, and national education regulations. The results of the study show that Christian Religious Education plays a strategic role in shaping the character of students so that they are able to live peacefully side by side in a pluralistic society. However, diversity education still tends to be limited to religious and ethnic aspects, while other dimensions such as cultural recognition, gender equality, democracy, and social justice have not been comprehensively integrated. Therefore, Christian Religious Education needs to be developed through a broader and more dialogical multicultural approach.